FRAX scores are increased in patients with ANCA-associated vasculitis - VELİOĞLU, ARZU; AŞICIOĞLU, EBRU; ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER; TUĞLULAR, ZÜBEYDE SERHAN (SPRINGER, 2021)
Purpose Prognosis in ANCA-associated vasculitis (AAV) has greatly improved with immunosuppressive use whereas incidence of treatment-related comorbidities such as osteoporosis has increased. However, studies investigating bone disease in AAV are limited. Fracture Risk Assesment Tool (FRAX) was developed to estimate 10-year hip and major osteoporotic fracture risks. Aim of this study was to estimate FRAX scores in AAV patients and compare them to healthy controls. Methods 30 AAV patients and 20 healthy controls were included. Demographic, disease, and medication history were recorded from patient files. Femoral neck, lumbar spine and forearm bone mineral densitometry, and thoracolumbar radiographs were performed. FRAX fracture risk scoring was assessed for all participants. Results There were 18 male and 12 female patients. Mean age was 58.5 +/- 11.7 years. Osteoporosis and osteopenia were present in 23.3% and 50% of patients, respectively. There were fractures in eight patients (26.7%). FRAX major fracture (9.4 +/- 7.3% vs 5.9 +/- 3.2%, p = 0.02) and hip fracture (2.2 +/- 3.2% vs 0.9 +/- 0.8%, p = 0.03) scores were higher in patients than controls. In seven (23.3%) patients, the 10-year probability of hip fracture was >= 3% and in five (16%) patients the 10-year risk of a major osteoporosis-related fracture was >= 20%. None of the controls exceeded these thresholds. Conclusion AAV patients are at high risk for future fractures as calculated with FRAX. Life-long monitoring for bone disease and fractures are essential. Large studies with longer follow-up are needed to determine the accuracy of FRAX risk scoring in predicting fractures.
Keywords: ANCA-associated vasculitis; FRAX; Bone fracture; Osteoporosis